2021
DOI: 10.3390/diagnostics11071195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endoscopic Ultrasound-Guided Tissue Acquisition on Decision-Making in Precision Medicine for Pancreatic Cancer: Beyond Diagnosis

Abstract: Precision medicine in cancer treatment refers to targeted therapy based on the evaluation of biomarkers. Although precision medicine for pancreatic cancer (PC) remains challenging, novel biomarker-based therapies, such as pembrolizumab, olaparib, and entrectinib, have been emerging. Most commonly, endoscopic ultrasound-guided tissue acquisition (EUS-TA) had been used for the diagnosis of PC until now. However, advances in EUS-TA devices and biomarker testing, especially next-generation sequencing, have opened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 173 publications
(199 reference statements)
0
13
0
Order By: Relevance
“…Another group of researchers, Wang et al [ 82 ], created a drug sensitivity model that is based on elastic net regression, an ML technique. ML algorithms have been shown to accurately predict medication susceptibility in gastric cancer [ 80 , 83 , 84 ], ovarian cancer [ 85 , 86 ], as well as endometrial cancer patients [ 87 ]. People diagnosed with tamoxifen, gastric cancer victims given with 5-FU, and endometrial cancer victims handled with paclitaxel are among those expected to be resilient by the model.…”
Section: Emerging Roles Of Artificial Intelligence In Cancer Drug Dev...mentioning
confidence: 99%
“…Another group of researchers, Wang et al [ 82 ], created a drug sensitivity model that is based on elastic net regression, an ML technique. ML algorithms have been shown to accurately predict medication susceptibility in gastric cancer [ 80 , 83 , 84 ], ovarian cancer [ 85 , 86 ], as well as endometrial cancer patients [ 87 ]. People diagnosed with tamoxifen, gastric cancer victims given with 5-FU, and endometrial cancer victims handled with paclitaxel are among those expected to be resilient by the model.…”
Section: Emerging Roles Of Artificial Intelligence In Cancer Drug Dev...mentioning
confidence: 99%
“…The application of artificial intelligence has also improved the performance of EUS, which can assist doctors in making more accurate diagnoses ( 51 ). EUS-FNA (endoscopic ultrasound fine-needle aspiration) has become a first-line method for the diagnosis of pancreatic cancer due to its high accuracy and few complications, with a sensitivity of over 90% ( 52 , 53 ). Biomarkers such as proteins and mRNAs enriched in EUS-FNA-derived fluid can be used to evaluate the expression of genes in the tumor microenvironment, providing the possibility of early diagnosis of pancreatic cancer ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al reported that patients with PC with homologous recombination deficiency (approximately 20 % of PC) are sensitive to platinum-containing chemotherapy 33 . Although third-generation EUS-guided fine needles have recently shown a higher histologic core procurement rate and higher success rate for genetic testing, the amount of samples is still limited 34 . The application of RSSF facilitates the creation of tumor organoids in patients with PC.…”
Section: Discussionmentioning
confidence: 99%